ANALYSIS OF INTERFACIAL AND MASS TRANSFER EFFECTS ON FORCED CONVECTION IN GAS-LIQUID ANNULAR TWO-PHASE FLOW - Nogueira, E.; Dantas, B. D.; Cotta, R. M. (Revista de Engenharia Térmica, 2004)
In a gas-liquid annular two-phase flow one of the main factors influencing the determination of heat transfer rates is the average thickness of the liquid film. A model to accurately represent the heat transfer in such situations has to be able of determining the average liquid film thickness to within a reasonable accuracy. A typical physical aspect in gas-liquid annular flows is the appearance of interface waves, which affect heat, mass and momentum transfers. Existing models implicitly consider the wave effects in the momentum transfer by an empirical correlation for the interfacial friction factor. However, this procedure does not point out the difference between interface waves and the natural turbulent effects of the system. In the present work, the wave and mass transfer effects in the theoretical estimation of average liquid film thickness are analyzed, in comparison to a model that does not explicitly include these effects, as applied to the prediction of heat transfer rates in a thermally developing flow situation.